ANALISIS RISIKO KREDIT DAN TINGKAT EFISIENSI OPERASIONAL TERHADAP PRFITABILITAS PADA KOPERASI DI KOTA MATARAM - Yanti, Ni Made Ayodia Ratna Dwi; Listiawati, Ni Putu; Pancawati, Ni Luh Putu Anom (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
The purpose of this study was to determine the effect of credit risk and the level of operational efficiency on the profitability of cooperatives in the city of Mataram. This study uses quantitative analysis with an associative approach. The type of data used is secondary data with data processing using the SPSS version 25.0 program. Data collection techniques used are observation and documentation. The samples used were five cooperatives with a purposive sampling technique with certain criteria. The data analysis used is multiple linear regression analysis with a determination coefficient of 55.90% on profitability. The results of the t-test stated that credit risk had no significant effect on profitability, while the level of operational efficiency had a significant effect on the profitability of cooperatives in the city of Mataram. The results of the F-test show that credit risk and the level of operational efficiency jointly affect the profitability of cooperatives in the city of Mataram.